RESEARCH OF MODERN ENVIRONMENTAL, SOCIAL AND ECONOMIC PROBLEMS OF SUSTAINABLE DEVELOPMENT OF THE REGION: COGNITIVE APPROACH - Z. N. Ismikhanov; Gamzat U. Magomedbekov (Юг России: экология, развитие, 2017)
Abstract. Aim. Conduct scenario modeling of the development of the social and economic system of the region fromthe standpoint of its sustainability. Material and methods. The basis of the work has been put data on the relation- ship of the main subsystems that form the socio-economic and environmental regional mechanism, the results of expert surveys, the annual statistical report on the socio-economic development of the region. Results. A cognitive map of the interrelationships of the main elements of the socioeconomic and ecological mechanism of the region, taking into account the specifics of the Republic of Dagestan, is constructed. The analysis of the stability of the social and economic system of the region regarding the feedback cycles for the indicator "natural environment", which showed that the system is not stable. The results of the scenario modeling of the development of the region showed that the regulatory role of the federal center is an important controlling factor for the region regarding its sustainabil- ity. The possibility of using scenario modeling for designing strategies for sustainable development of the region on the basis of cognitive structuring of the development of possible situations is shown. Conclusion. The opportunities for cognitive structuring of knowledge about the problem situation are significant for developing scenarios for the development of the region from the standpoint of its sustainability and designing strategies for the sustainable development of its socio-economic system based on them. The most significant stage in the study of this problem is the collection of information, and its structuring in the form of a cognitive map.